Distortion through modeling asymmetric bargaining power - Haake, Claus-Jochen; Streck, Thomas
We study the consequences of modeling asymmetric bargaining power in two-person bargaining problems. Comparing application of an asymmetric version of a bargaining solution to an upfront modification of the disagreement point, the resulting distortion crucially depends on the bargaining solution concept. While for the Kalai-Smorodinsky solution weaker players benefit from modifying the disagreement point, the situation is reversed for the Nash bargaining solution. There, weaker players are better off in the asymmetric bargaining solution. When comparing application of the asymmetric versions of the Nash and the Kalai-Smorodinsky solutions, we demonstrate that there is an upper bound for the weight of a player, so that she is better off with the Nash bargaining solution. This threshold is ultimately determined by the relative utilitarian bargaining solution. From a mechanism design perspective, our results provide valuable information for a social planner, when implementing a bargaining solution for unequally powerful players.
Keywords: Asymmetric bargaining power; Nash bargaining solution; Kalai-Smorodinsky bargaining solution

Network Disruption and the Common-Enemy Effect - Hoyer, Britta; De Jaegher, Kris (International Journal of Game Theory)

Differences in NPI strategies against COVID-19 - Redlin, Margarete (Journal of Regulatory Economics)
Abstract Non-pharmaceutical interventions are an effective strategy to prevent and control COVID-19 transmission in the community. However, the timing and stringency to which these measures have been implemented varied between countries and regions. The differences in stringency can only to a limited extent be explained by the number of infections and the prevailing vaccination strategies. Our study aims to shed more light on the lockdown strategies and to identify the determinants underlying the differences between countries on regional, economic, institutional, and political level. Based on daily panel data for 173 countries and the period from January 2020 to October 2021 we find significant regional differences in lockdown strategies. Further, more prosperous countries implemented milder restrictions but responded more quickly, while poorer countries introduced more stringent measures but had a longer response time. Finally, democratic regimes and stronger manifested institutions alleviated and slowed down the introduction of lockdown measures.
Keywords: Economics and Econometrics

Modelling artificial intelligence in economics - Gries, Thomas; Naudé, Wim (Journal for Labour Market Research)
Abstract We provide a partial equilibrium model wherein AI provides abilities combined with human skills to provide an aggregate intermediate service good. We use the model to find that the extent of automation through AI will be greater if (a) the economy is relatively abundant in sophisticated programs and machine abilities compared to human skills; (b) the economy hosts a relatively large number of AI-providing firms and experts; and (c) the task-specific productivity of AI services is relatively high compared to the task-specific productivity of general labor and labor skills. We also illustrate that the contribution of AI to aggregate productive labor service depends not only on the amount of AI services available but on the endogenous number of automated tasks, the relative productivity of standard and IT-related labor, and the substitutability of tasks. These determinants also affect the income distribution between the two kinds of labor. We derive several empirical implications and identify possible future extensions.
Keywords: General Medicine

The Market for Belief Systems: A Formal Model of Ideological Choice - Gries, Thomas; Müller, Veronika; Jost, John T. (Psychological Inquiry)
Keywords: General Psychology

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Manipulation durch Fake-Bewertungen: Einfluss von Such- und Erfahrungsgütern auf das manipulative Verhalten des Verkäufers - N., N.

An Analysis of Coalition Formation Methods to achieve Maximum Social Surplus - N., N.

Die Möglichkeiten der Blockchain-Technologie im Supply Chain Management - eine spieltheoretische Analyse - N., N.

Kindergarten Allocation and the Tradeoff between Stability and Diversity Considerations - N., N.

Effect of the Agent's bargaining positions in the efficiency of matching markets - N., N.

Stabile Zuordnung mit Paaren - Der neue NRMP Algorithmus - N., N.

School choice with reserves and quotas - N., N.

Organisation von Zeitbörsen - N., N.

Wage Bargaining and Employment Revisited: Separability and Efficiency in Collective Bargaining - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya (Scandinavian Journal of Economics)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow (1981). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of Independence of Irrelevant Alternatives is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems---and thus helps to facilitate real-world negotiations.
Keywords: Labour market negotiations; efficient bargains; Nash bargaining solution; sequential bargaining; restricted bargaining games

Late-Career Unemployment and Cognitive Abilities - Freise, Diana; Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)
We study the effect of unemployment on cognitive abilities among individuals aged between 50 and 65 in Europe. To this end, we exploit plant closures and use flexible event-study estimations together with an experimentally elicited measure of fluid intelligence, namely word recall. We find that, within a time period of around eight years after the event of unemployment, cognitive abilities only deteriorate marginally — the effects are insignificant both in statistical and economic terms. We do, however, find significant effects of late-career unemployment on the likelihood to leave the labor force, and short-term effects on mental health problems such as depression and sleep problems.

Marginal College Wage Premium under Selection into Employment - Westphal, Matthias; Kamhöfer, Daniel A.; Schmitz, Hendrik (Economic Journal)

Spring Forward, Don't Fall Back: The Effect of Daylight Saving Time on Road Safety - Bünnings, Christian; Schiele, Valentin (The Review of Economics and Statistics)
In this paper, we analyze the effect of light conditions on road accidents and estimate the long run consequences of different time regimes for road safety. Identification is based on variation in light conditions induced by differences in sunrise and sunset times across space and time. We estimate that darkness causes annual costs of more than £500 million in Great Britain. By setting daylight saving time year-round 8 percent of these costs could be saved. Thus, focusing solely on the short run costs related to the transition itself underestimates the total costs of the current time regime.

Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.

Educational Assimilation of First-Generation and Second-Generation Immigrants in Germany - Gries, Thomas; Redlin, Margarete; Zehra, Moonum (Journal of International Migration and Integration)
Abstract Using data from the German Socio-Economic Panel for 1984–2018, we analyze the intergenerational education mobility of immigrants in Germany by identifying the determinants of differences in educational stocks for first- and second-generation immigrants in comparison to individuals without a migration background. Our results show that on average, first-generation immigrants have fewer years of schooling than native-born Germans and have a disproportionate share of lower educational qualifications. This gap is strongly driven by age at immigration, with immigration age and education revealing a nonlinear relationship. While the gap is relatively small among individuals who migrate at a young age, integrating in the school system at secondary school age leads to large disadvantages. Examining the educational mobility of immigrants in Germany, we identify an inter-generational catch-up in education. The gap in education between immigrants and natives is reduced for the second generation. Finally, we find that country of origin differences can account for much of the education gap. While immigrants with an ethnic background closer to the German language and culture show the best education outcomes, immigrants from Turkey, Italy, and other southern European countries and especially the group of war refugees from Syria, Afghanistan, Iraq and other MENA countries, have the lowest educational attainment.

Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas; Fritz, Marlon (Journal of Nonparametric Statistics)

Modern sector development: The role of exports and institutions in developing countries - Gries, Thomas; Grundmann, Rainer (Review of Development Economics)

Gender, competitiveness, and task difficulty: Evidence from the field - Hoyer, Britta; van Huizen, Thomas; Keijzer, Linda; Rezaei, Sarah; Rosenkranz, Stephanie; Westbrock, Bastian (Labour Economics)
This study examines the gender gap in competitiveness in an educational setting and tests whether this gap depends on the difficulty of the task at hand. For this purpose, we administered a series of experiments during the final exam of a university course. We confronted three cohorts of undergraduate students with a set of bonus questions and the choice between an absolute and a tournament grading scheme for these questions. To test the moderating impact of task difficulty, we (randomly) varied the difficulty of the questions between treatment groups. We find that, on average, women are significantly less likely to select the tournament scheme. However, the results show that the gender gap in tournament entry is sizable when the questions are relative easy, but much smaller and statistical insignificant when the questions are difficult.

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.

Determinants of nursing home choice: Does reported quality matter? - Schmitz, Hendrik; Stroka‐Wetsch, Magdalena A. (Health Economics)
Keywords: Health Policy

Early Disclosure of Invention and Reduced Duplication: An Empirical Test - Lück, Sonja; Balsmeier, Benjamin; Seliger, Florian; Fleming, Lee (Management Science)
Much work on innovation strategy assumes or theorizes that competition in innovation elicits duplication of research and that disclosure decreases such duplication. We validate this empirically using the American Inventors Protection Act (AIPA), three complementary identification strategies, and a new measure of blocked future patent applications. We show that AIPA—intended to reduce duplication, through default disclosure of patent applications 18 months after filing—reduced duplication in the U.S. and European patent systems. The blocking measure provides a clear and micro measure of technological competition that can be aggregated to facilitate the empirical investigation of innovation, firm strategy, and the positive and negative externalities of patenting. This paper was accepted by Joshua Gans, business strategy.
Keywords: Management Science and Operations Research; Strategy and Management

Introduction to the Special Issue “Bargaining” - Haake, Claus-Jochen; Trockel, Walter (Homo Oeconomicus)
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarbøe, Odvar M. (Journal of Economic Behavior & Organization)
Many countries have opened their health care markets to private for-profit providers, aiming to promote quality and choice for patients. The prices are regulated and providers compete in location and quality. We show that whereas opening a public hospital market typically raises quality, the private provider strategically locates towards the corner of the market to avoid costly quality competition. Social welfare depends on the size of the regulator's budget and on the altruism of the public provider. If the budget is large, high quality results and welfare is highest in a duopoly whenever entry is optimal. If the budget is small, quality levels in a duopoly mirror the quality level in a monopoly. It can be optimal for the regulator not to use the full budget.

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Zuordnungsverfahren für Tauschbörsen - N., N.

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.